Failure behavior of an adaptive concrete beam with integrated fluidic actuators: non-linear three-dimensional finite element analysis - Gambarelli, Serena; Fararoni Platas, R. Noé; Shankar, Arvinth; Dakova, Spasena; Böhm, Michael; Sawodny, Oliver; Nitzlader, Markus; Blandini, Lucio (Frontiers in Built Environment, 2023)
In the present study, the adaptive behavior of a concrete beam with integrated fluidic actuators was numerically investigated through three-dimensional (3D) non-linear finite element (FE) analysis. The employed numerical approach for the mechanical behavior of concrete is based on the microplane theory, implemented in the in-house software MAcroscopic Space Analysis (MASA). Different cases were analyzed and the results compared with experimental tests available in the literature. First, a reference concrete beam without actuators was numerically analyzed in order to calibrate and validate the employed non-linear microplane material model. Thereafter, the validated model was used for the non-linear analysis of the concrete beam with integrated fluidic actuators, with respect to different load cases. The obtained results confirm the capability of the model to reproduce the deformational behavior of the beam for all analyzed cases. A fundamental aspect is the realistic modeling of the actuators and related applied pressure. The use of a non-linear material model allows to realistically capture the possible cracking and consequent failure of the beam. It is worth mentioning that a full model validation should be extended to the long-term behavior of actuated structural elements. In future perspective, the well-established numerical framework for concrete, based on coupled 3D hygro-thermo-mechanical model, can be used to (1) investigate the performance of adaptive structural components, with respect to more complex loading conditions, e.g. cyclic; (2) perform durability analysis under exposure to different combinations of mechanical and/or environmental loading conditions.